Karakteristik Penderita Degenerasi Makula Karena Usia di Klinik Mata SMEC Samarinda Periode 2018-2022: Characteristics of Patients Age Related Macular Degeneration at the Samarinda SMEC Eye Clinic for the Period 2018-2022 - Rimayanti, A. Annisa Aulia; Fatmawati, Nur Khoma; Sawitri, Endang; Putra, Indra Sukmana (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2024)
Age-related macular degeneration which is a neurological disease that progresses over time and affects the macula. The purpose of this research was to identify the characteristics of patients diagnosed with age-related macular degeneration who were treated at the SMEC Eye Clinic Samarinda between the years 2018 and 2022. The study was descriptive-observational in nature and applied a cross-sectional method. It made use of secondary data obtained from the medical records of 335 patients diagnosed with age-related macular degeneration who were treated at SMEC Eye Clinic Samarinda between 2018 and 2022. The study found that the majority of patients with age-related macular degeneration during the period 2018-2022 were males, totaling 187 patients (53%). The highest age group was the 60-69 age group, with 145 patients (43%). The involvement of the eyes was predominantly unilateral, with 211 patients (64%), and the most common visual acuity among patients was <6/18-?6/60 or moderate visual impairment, with 180 eyes (39%). Keywords: Age Related Macular Degeneration, Gender, Side Eye, Age, Vision Abstrak Degenerasi makula karena usia atau age related macular degeneration adalah suatu penyakit neurodegeneratif yang bersifat progresif dan mengenai pada makula. Penelitian ini bertujuan untuk mengetahui karakteristik penderita degenerasi makula karena usia di Klinik Mata SMEC Samarinda periode 2018-2022. Penelitian bersifat deskriptif dengan pendekatan cross sectional menggunakan data sekunder berupa rekam medik populasi terjangkau, yaitu 335 penderita degenerasi makula karena usia di klinik Mata SMEC Samarinda dalam periode 2018-2022. Penelitian ini mendapatkan penderita degenerasi makula karena usia terbanyak ialah berjenis kelamin laki-laki sebanyak 187 penderita (53%). Kelompok usia tertinggi ialah usia 60-69 tahun sebanyak 145 penderita (43%). Sisi mata yang terkena ialah unilateral sebanyak 211 penderita (64%) dan visus terbanyak penderita ialah <6/18-?6/60 atau gangguan penglihatan sedang sebanyak 180 mata (39%). Kata Kunci: Degenerasi Makula Karena Usia, Jenis Kelamin, Sisi Mata Yang Terkena, Usia, Visus